La formación del docente en adaptaciones curriculares para la atención a estudiantes con discapacidad intelectual en instituciones regulares - Barahona Cruz, Dayana Madelayne (2021)
The present investigation established with the theme "Teacher training in curricular adaptations for the care of students with intellectual disabilities in regular institutions" starts from a reality that has been experienced over time; According to public policies and current educational reforms, inclusive education constantly poses new challenges for the teacher, in such a way that due to ignorance of how to make an adequate approach, it can become a limiting agent for the educational process of students with disabilities. intellectual disability. The research has been carried out in the ordinary institutions of the 09D10 Juan Gómez Rendón - Progreso district, in the Juan Gómez Rendón parish, Guayaquil canton, with students with mild and moderate intellectual disabilities. The type of research used in the present research was descriptive where fundamental aspects were referred according to the information collected with the instruments such as: interviews, surveys and questionnaires…….